Antimicrobial Effects of Chemically Functionalized and/or Photo-Heated Nanoparticles - Pezzi, Luigia (Materials (Basel), 2019)
Antibiotic resistance refers to when microorganisms survive and grow in the presence of specific antibiotics, a phenomenon mainly related to the indiscriminate widespread use and abuse of antibiotics. In this framework, thanks to the design and fabrication of original functional nanomaterials, nanotechnology offers a powerful weapon against several diseases such as cancer and pathogenic illness. Smart nanomaterials, such as metallic nanoparticles and semiconductor nanocrystals, enable the realization of novel drug-free medical therapies for fighting against antibiotic-resistant bacteria. In the light of the latest developments, we highlight the outstanding capabilities of several nanotechnology-inspired approaches to kill antibiotic-resistant bacteria. Chemically functionalized silver and titanium dioxide nanoparticles have been employed for their intrinsic toxicity, which enables them to exhibit an antimicrobial activity while, in a different approach, photo-thermal properties of metallic nanoparticles have been theoretically studied and experimentally tested against several temperature sensitive (mesophilic) bacteria. We also show that it is possible to combine a highly localized targeting with a plasmonic-based heating therapy by properly functionalizing nanoparticle surfaces with covalently linked antibodies. As a perspective, the utilization of properly engineered and chemically functionalized nanomaterials opens a new roads for realizing antibiotic free treatments against pathogens and related diseases.